Evaluasi Tingkat Pengetahuan Ibu Hamil terhadap Pentingnya Asam Folat pada Kehamilan di RSAU Lanud Sulaiman Bandung - Diana Fitrisari; Rida Emelia (Syntax Corporation Indonesia, 2021)
Folic acid for pregnant women which plays an important role in the formation of one-third of red blood cells and vitamins that are good during pregnancy for baby and pregnant women. According to the World Health Organization (WHO) in 2010 showed that about 56% of all types of anemia are thought to be due to iron deficiency. In addition, 36% due to micronutrient deficiencies (vitamins A, B6, B12, riboflavin and folic acid) and the remaining 8% due to hereditary factors such as thaasemia and cyclical cell disease have also been known to cause anemia (Fatimah, 2011). A study was conducted with the title profile of the level of knowledge of pregnant women on the importance of folic acid in pregnancy at a hospital in Bandung on April 5-5 June 2021 with the aim of knowing the level of knowledge of pregnant women on folic acid in pregnancy